Health Monitoring KIOSK: An effective system for ru ral health management - Rajalaxmi Das; Himansu Mohan Padhy (International Journal of Innovations in Engineering Research and Technology, 2021)
In the rural areas of our country, patients went to the public health centers (PHC) for their treatmen t. PHCs in India are allotted with hardly one doctor. It is really difficult at a single doctor’s end to provi de treatment to huge number of patients approaching a single doc tor. Therefore, in this work it is proposed to deve lop an automated diagnosis system by developing a Health K IOSK.